COVID-19 quarantine: Psychological impact and support for children and parents - Francesco Demaria; Stefano Vicari (BMC, 2021)
Abstract In response to the coronavirus (COVID-19) pandemic, national governments have imposed urgent sanitary and social measures to control the spread of the virus. One such measure is quarantine, which involves restricting people's movement through the isolation of infected or suspected infected individuals in order to reduce the risk of new infections. Research has shown that quarantine is a psychologically stressful experience. With respect to children, lack of school and interruptions to daily routines could have a negative impact on their physical and mental health. Parents may also pass their psychological distress to children and practice inappropriate parenting behaviors, which could contribute to the development of post-traumatic stress symptoms in children. In order to prevent these negative outcomes, governments must carefully consider any their decision to impose quarantine and family social care services must work together with children's mental health services to ensure that the experience is as tolerable and safe as possible.